Penegakan Hukum Administrasi Negara Terhadap Pengolahan Limbah Bahan Berbahaya dan Beracun Industri Pengasapan Karet di Kota Jambi - Fanny Inayah, Rts.; Budhiartie, Arrie; Mushawirya, Rustian (Fakultas Hukum Universitas Jambi, 2022)
This article discusses the Enforcement of State Administrative Law Against Hazardous Waste Treatment in the Crumb Rubber Industry in Jambi City. The purpose of this study was to determine the proper and proper mechanism for processing hazardous waste in the rubber smoking industry, in addition to knowing the government's legal actions against perpetrators of violations of hazardous waste processing in Jambi City. The research method used is empirical juridical, namely research that emphasizes in terms of observation, which seeks to observe legal facts that apply in society, where it requires knowledge to be observed and proven openly. The results of the study indicate that there is a conflict between das sollen and das sein regarding the treatment of B3 waste from the Rubber Smoking Industry in Jambi City in accordance with Jambi City regulations Number 7 of 2017 which states that the location for storing B3 waste is required to be free from flooding and not prone to natural disasters. there are buildings that are rusty, emitting noise, vibration and also the smell produced by the B3 waste. Therefore, it is necessary for the government's role in the B3 waste treatment mechanism in accordance with applicable regulations and the government's role in providing administrative law enforcement against perpetrators of B3 Waste Treatment violations.